Conceptualizing educational resilience during the COVID-19 pandemic - Aleghfeli, YK (Indian Association for Career and Livelihood Planning, 2021)
In March 2020, the COVID-19 outbreak was declared a global pandemic, prompting an unprecedented series of mandatory lockdowns across countries around the world (WHO, 2020). In a month’s time, the COVID-19 pandemic resulted in school closures affecting 180 countries and causing 85% of students worldwide to be out of school (World Bank, 2020). Low and Middle Income Countries (LMICs) were hit harder than High Income Countries (HICs). The global crisis prompted international development agencies to collaborate and commission several large-scale studies to understand the full extent of national educational systems’ vulnerability to disruption risk and evaluate their potential to be resilient against future disruptions, such as climate change and other natural or man-made disasters. The aim of this paper is to examine international development agencies’ engagement with the term, educational resilience, during the COVID-19 pandemic and its implications on academic discourse around educational resilience. The paper starts with a literature review on how educational resilience evolved as a concept within the four waves of resilience research. The paper then presents findings from four large-scale studies produced by several international development agencies in response to the COVID-19 pandemic and examine how they engaged with the concept of educational resilience. The discussion rounds out the paper by linking international development agencies’ engagement of educational resilience to the academic discourse to emphasize the need for a more robust conceptualization of educational resilience that can address vulnerability to disruption risk.